Handbook of fluid sealing - Brink, Robert V. (McGraw-Hill, 1993)
A reference on the design, application, testing and manufacture of seals and gaskets for static and dynamic fluid sealing. It examines state-of-the-art practices in materials selection, test techniques, instrumentation developments, and mathematical tools for making informed sealing decisions